The thymus microenvironment in regulating thymocyte differentiation - Gameiro, Jacy (Landes Bioscience, 2010)
The thymus plays a crucial role in the development of T lymphocytes by providing an inductive microenvironment in which committed progenitors undergo proliferation, T-cell receptor gene rearrangements and thymocyte differentiate into mature T cells. The thymus microenvironment forms a complex network of interaction that comprises non lymphoid cells (e.g., thymic epithelial cells, TEC), cytokines, chemokines, extracellular matrix elements (ECM), matrix metalloproteinases and other soluble proteins. The thymic epithelial meshwork is the major component of the thymic microenvironment, both morphologically and phenotypically limiting heterogeneous regions in thymic lobules and fulfilling an important role during specific stages of T-cell maturation. The process starts when bone marrow-derived lymphocyte precursors arrive at the outer cortical region of the thymic gland and begin to mature into functional T lymphocytes that will finally exit the thymus and populate the peripheral lymphoid organs. During their journey inside the thymus, thymocytes must interact with stromal cells (and their soluble products) and extracellular matrix proteins to receive appropriate signals for survival, proliferation and differentiation. The crucial components of the thymus microenvironment, and their complex interactions during the T-cell maturation process are summarized here with the objective of contributing to a better understanding of the function of the thymus, as well as assisting in the search for new therapeutic approaches to improve the immune response in various pathological conditions.